Neointimal hyperplasia: are fatty acid transport proteins a new therapeutic target?. Issue 5 (October 2019) - Rekhi, Umar; Piche, Julia E.; Immaraj, Linnet; Febbraio, Maria
Abstract : Purpose of review: High-fat diets contribute to hyperlipidemia and dysregulated metabolism underlying insulin resistant states and cardiovascular diseases. Neointimal hyperplasia is a significant resulting morbidity. Increased fatty acid (FA) levels lead to dysfunctional endothelium, defined as activated, proinflammatory and prothrombotic. The purpose of this review is to assess the recent literature on the emerging concept that uptake of FA into many tissues is regulated at the endothelial level, and this in turn contributes to endothelial dysfunction, an initiating factor in insulin resistant states, atherosclerosis and neointimal hyperplasia. Recent findings: Studies support the role of endothelial FA uptake proteins as an additional level of regulation in tissue FA uptake. These proteins include CD36, FA transport proteins, FA-binding proteins and caveolin-1. In many cases, inappropriate expression of these proteins can result in a change in FA and glucose uptake, storage and utilization. Accumulation of plasma FA is one mechanism by which alterations in expression of FA uptake proteins can lead to endothelial dysfunction; changes in tissue substrate metabolism leading to inflammation are also implicated. Summary: Identification of the critical players and regulators can lead to therapeutic targeting to reduce endothelial dysfunction and sequela such as insulin resistance and neointimal hyperplasia.